The development of information in daily life / Puteri Lu'lu Fahrin Shah and Nur Hidayyah Shari Shawarudin - Fahrin Shah, Puteri Lu'lu; Shari Shawarudin, Nur Hidayyah (Faculty of Information Management, 2015)
Improved quality of life and increase the country's cost of living has become a hot issue among users. The most important step towards more practical and advanced is the use of preferential measures for the use of information technology. Housing and services is a branch of the municipal economic and infrastructure is an essential part of a more sustainable life, determining comfort to human life activities. In today's world of increasingly sophisticated and modern, the information is a resource that is becoming increasingly important especially in our lives. Information also does not have strict control. Human beings as users want an easy life and easy to work.